IOT Based Security System Using RFID Tags - J.Selvin Paul Peter, Mehul Singh, SarthakVerma (International Journal of Advanced Science and Technology, 2020)
Our focus is on building a Security Gate Management System with integrated Parking System for entities (Companies, colleges etc.) where there is a in and out flow of more than 200 vehicles. The technology uses RFID tag system with an integrated Server which essentially saves all the information of the gate passers. After Vehicle identification, the automated parking system points to the nearest empty parking block to the gate passer using Infrared technology. The objective is to reduce Human Interactions in Security gate management systemKeywords: Radio Frequency identification (RFID), RFID reader, RFID tag, Infrared red sensor, Embedded Systems.